PSIV-13 Examining feedlot performance of Angus sired steers implanted with estradiol, trenbolone acetate, or a combined implant. (30th November 2020) - Reichhardt, Caleb C; Brady, Tevan J; Briggs, Reganne K; Smith, Laura A; Bowman, Brett; Thomas, Aaron; Thornton, Kara J
Abstract: The goal of this research was to examine feedlot performance of steers receiving implants with different hormone composition. Fifty Angus sired steers were initially blocked by weight and placed into one of four implant treatment groups: no implant (CON), estrogen (E2 ; Compudose; 25.7 mg estradiol; Elanco Animal Health; Greenfield, IN), androgen (TBA; Finaplix H; 200 mg trenbolone acetate; Merck Animal Health; Madison, NJ), and a combination of estrogen and androgen (ETBA; Revalor-S; 120 mg trenbolone acetate + 24 mg estradiol; Merck Animal Health). Steers were randomly placed into pens equipped with GrowSafe® bunks and fed the same ration. Steers were weighed and ultra-sounded on days 0, 28, 56, 84, and 112. Blood was collected on days 0, 2, 10, 28, 56, 84, and 112. Average daily gain (ADG), backfat (BF), and weights were collected. Data were analyzed with day as a repeated measure using the ProcMixed procedure to test the main effect of implant. Both treatment and day had effects on weight of the steers (P < 0.05) indicating that steers receiving ETBA gained more (P < 0.05) than the CON or E2 steers. Steers implanted with ETBA or TBA had an increased (P < 0.05) ADG when compared to the CON steers. There was no effect (P > 0.05) of treatment or treatment*day on BF; however, BF did increase (P < 0.05) over time. The information gathered from this trial corroborates that implants are an effective tool to increase overall growth of angus sired steers in feedlots and that a combined implant results in increased weight gain when compared to an E2 only implant or non-implanted animals. Future work is going to examine the transcriptional and post-transcriptional mechanisms that improve growth of steers implanted with E2, TBA, or ETBA implants.